The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1039/d1ra00114k
|View full text |Cite
|
Sign up to set email alerts
|

High acetone sensing properties of In2O3–NiO one-dimensional heterogeneous nanofibers based on electrospinning

Abstract: The In2O3–NiO nanofiber with p–n heterojunctions exhibited an enhanced acetone sensing performance, and the detection limit reached 10 ppb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…According to the ratios, the selectivity of the sensor depends on the sensitivity of different gases, and the sensitivity of different gases is related to the reaction intensity of the gas on the surface of the sensing material. Due to the reaction intensity being influenced by the amount of adsorbed gas on the surface and the reaction energy, the material composition and working temperature are key factors to determine the selectivity, and the sensor exhibits the highest reaction intensity at the optimal operating temperature [13]. Compared with Co 3 O 4 , the acetone reaction intensity on the surface of CZ-2 is enhanced more than other gases, resulting in improved selectivity.…”
Section: Gas-sensing Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the ratios, the selectivity of the sensor depends on the sensitivity of different gases, and the sensitivity of different gases is related to the reaction intensity of the gas on the surface of the sensing material. Due to the reaction intensity being influenced by the amount of adsorbed gas on the surface and the reaction energy, the material composition and working temperature are key factors to determine the selectivity, and the sensor exhibits the highest reaction intensity at the optimal operating temperature [13]. Compared with Co 3 O 4 , the acetone reaction intensity on the surface of CZ-2 is enhanced more than other gases, resulting in improved selectivity.…”
Section: Gas-sensing Propertiesmentioning
confidence: 99%
“…Therefore, enhanced sensing properties can be obtained by constructing a heterojunction. The structures of heterogeneous materials include a hybrid heterostructure, a decorated heterostructure, and a multilayer heterostructure [13][14][15][16]. Among them, the decorated heterostructure is beneficial for gas sensing due to its good synergistic effect between the core and shell components and larger heterointerface [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…and/or p-type (CuO, NiO, Co 3 O 4 etc.) metal oxides that show different sensing properties depending on the way they are formed. Various studies revealed that the existence of such heterojunctions facilitates gas sensing phenomenon by electron/hole movement through the interface modulated potential barrier. When two different metal oxides are in physical contact, the Fermi level of the hybrid material must align.…”
Section: Oxide Heterostructure For Gas Sensingmentioning
confidence: 99%
“…However, inhaling acetone is harmful, especially to the nervous system, and further propagates narcosis, headache, and fatigue. In addition, acetone is one of the byproducts of mammalian metabolism, in which the breath acetone levels escalate to more than 1800 ppm for patients with diabetes mellitus and a few hundred ppm during high ketogenic diets. Therefore, it is important to sense acetone concentration accurately from both industrial and healthcare perspectives to raise an alarm about the exposure levels. Essentially, the active component in the acetone sensor is made of nanostructures of ZnO, , SnO 2, TiO 2, , WO 3, In 2 O 3, and Fe 2 O 3 and the composite of graphene and polyaniline (PANI) . Typically, these materials show a change in electrical resistance in the presence of a reducing gas such as acetone, realized as ideal for electrical/electrochemical sensor development.…”
Section: Introductionmentioning
confidence: 99%